Sistem Pengendalian Manajemen Dan Perilaku Dysfunctional Satuan Kerja Perangkat Daerah Provinsi Banten - tri lestari; Lili Sugeng Wiyantoro (Universitas Serang Raya, 2019)
This study aims to investigate the impact of standard operating procedures, budget participation, and budget control on dysfunctional behaviour of Satuan Kerja Perangkat Daerah (SKPD) at Banten Province. The population of this study is the chief officers at all districts and cities in Banten area. We select the officers who involved in reconstructing the planning and using Sistem Informasi Keuangan Daerah (SIKD), which consist of the head of department, the head of field, the head of financial, accounting and budget planning division. The data were collected by using questioner and analyzed by using SmartPLS (Partial Least Square). The results show that those management control tools have an impact on dysfunctional behavior of SKPD. We found that a better standards operating procedures of SKPD could reduce the dysfuctional behavior. The more involvement of SKPD in budget planning, the more dysfunctional behavior could avoid. Finally, dysfunctional behavior could decrease by using budget control for positive intention.